Quality Control Improvement Using Seven Tools And Six Sigma Methods At Pt. Xyz - Anthony Septian; Leni; Anita Christine Sembiring (Institute of Computer Science (IOCS), 2022)
Quality is an important topic for debate in a company because the facts on the ground show that a successful and surviving company must have quality control. Based on observations made at PT. XYZ, which is located in the Medan Marelan area, North Sumatra, it can be seen that the problem being faced by this company is the number of defective products produced during the production process. Therefore, this study aims to provide suggestions and reviews of improving quality control by implementing it using the seven tools method. Control analysis using seven tools method, namely check sheet, histogram, Pareto diagram, cause and effect diagram, control chart. This study took a sample of 50 pcs in 25 takers with 109 defective products. There are 4 types of defects in this study, namely: torn packaging defects, crushed processing defects, inappropriate weight defects, mixed processing defects. In the analysis, it was found that the biggest defects were in the torn packaging (40%) and crushed processing (38%). The results of the study of cause and effect diagrams found that the influence of labor, machinery, materials was the main point that had to be improved. In making the control chart Clp does not cross the UCLp and LCLp lines so that statistically out of control process variations are not found. Because there are no process variations that are outside the control limits, no revision is needed. Thus the process is in control. This study also uses the six sigma method to calculate the DPMO value and see the sigma level of companies in the industrial world. The result of the calculation is that the DPMO value in the company is 21,800 with a defect value of around 27%. It can be stated that the company has an average level of 3, which is above the Indonesian industry average. This is included in a fairly good level.